Improving model-based learning activities approach To incease student motivation in aqeedah morals at Seventh grade students in m.t.s.n kayu kalek district Of kambang - Siul Siul (Jurnal Ilmiah Pendidikan Scholastic, 2017)
The problem in this research is the low motivation to study moral theology in M. TS .N Kayu Kalek District of Kambang This study aims to increase students' motivation on the subjects of moral theology using activity-based learning model. The type of research used is classroom action research (PTK) which has been done in three cycles. Subjects in the study This is a classVII MTsN Kayu Kalek District of Kambang totaling 21person. The object of his research is Based learning model activity. The research methods used by researchers in This research uses classroom action research method with qualitative descriptive approach that is trying to describe theexisting problem solving based on qualitative descriptive technique. Based on the value of the end test cycle, there is an increase from cycle I, to cycle II and cycle III. In the first cycle the average score of students is 75, the second cycle is the average score of 79 students, and in cycle III it has a very good improvement with the average score of 87. in terms of percentage of students' learning mastery in one class, II is higher than cycle I andcycle III Higher than cycle II, ie in cycle I with value 75, cycle II 79, and cycle III 87, then this can be said satisfactory so that the outcome of this cycle III has exceeded the target within Research, so no need to continue in the cyclenext. Based on the hypothesis it can be concluded that the model Activity-based learning can improve achievement motivation and mastery of students' concepts of Aqidah subjects Morals subject of attributes of Allah in M.TS.N Kayu Kalek District of Kambang.